PRACTICING TEXT SUMMARY WITH ONLINE E-BOOK SYSTEM - Wang, B; Yu, P (PEOPLE: International Journal of Social Sciences, 2015)
The improvement of information and communication technology (ICT) enhance the change of reading behavior from printed books to e-books. The prevalence of internet also encourages the prosperity of online e-book reading. The present study proposed an online e-book reading system that could import reading content in “EPUB” format and export the modified content in “EPUB” format as well. It did not only provide reading and noting tools for reading activities but also utilized the concept of online learning and scaffolding theory to build a model of scaffolding with summary practice. When students were asked to do the summary practice, they simply used the selecting and highlighting tool to identify keywords or main ideas among these texts. Then, teachers guided these students to learn the principle of summary construction through online interaction. The monitoring tool informed teachers to realize the progress of students and adjusted the way of guiding students in selecting keywords ubiquitously. The system is capable of displaying the combined text highlights that marked by students and teachers. Then students might correct and improve their works under such a visual comparison policy. The system also embeds scaffolding functions that can support teachers to setting online learning stages for summary practice.